2007
DOI: 10.1007/s10654-007-9111-8
|View full text |Cite
|
Sign up to set email alerts
|

Lack of association between genetic variants in the mannose-binding lectin 2 (MBL2) gene and HPV infection

Abstract: Genetic variants in the immunomodulatory gene mannose-binding lectin 2 (MBL2), were associated with risk, severity, and frequency of viral infections. In a case-control setting, we investigated the association of MBL2 functional polymorphisms with Human Papillomas Virus (HPV) infection. No differences between cases (HPV(+)) and controls (HPV(-)) were found in the distribution of each single genotypes or allele. Haplotype analysis did not show any difference between HPV+ and HPV(-) groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 9 publications
1
8
2
Order By: Relevance
“…The relative weakness of MBL2 association to HPV infection could contribute to explain the difference between our findings and those of Parrella et al [18], who demonstrated a lack of association between MBL2 SNPs and HPV infection in Italian women.…”
Section: Discussioncontrasting
confidence: 99%
“…The relative weakness of MBL2 association to HPV infection could contribute to explain the difference between our findings and those of Parrella et al [18], who demonstrated a lack of association between MBL2 SNPs and HPV infection in Italian women.…”
Section: Discussioncontrasting
confidence: 99%
“…Our findings are not in agreement with those obtained by Parrella et al [15], who did not find any correlation between genetic variants in the MBL2 gene and susceptibility to HPV infection. It should be noted, however, that Parrella et al analyzed a group of patients with a different ethnic background (Caucasian) from our study population (Brazilian) and that their MBL2 genotype and allelic frequencies were quite different from those reported in the NCBI database for the Caucasian population.…”
Section: Discussioncontrasting
confidence: 99%
“…Several reports suggest that MBL can also modulate the disease severity and can be used as a marker to predict the therapeutic efficacy in some disorders, such as the response to interferon treatment in patients with chronic hepatitis C [14]. To our knowledge only one recent paper has investigated a possible correlation between MBL2 functional polymorphisms and susceptibility to HPV infection, reporting negative findings and the lack of an association [15].…”
Section: Introductionmentioning
confidence: 99%
“…There are only few reports regarding the association between HPV and MBL [9][10][11][12]. Some authors showed that certain polymorphisms in the MBL2 gene were associated with higher susceptibility to infection by high-risk HPV genotypes [10][11][12].…”
Section: Introductionmentioning
confidence: 99%